PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL DAN PERILAKU BELAJAR PADA TINGKAT PEMAHAMAN AKUNTANSI - Rusmiani, Ni Kadek Ayu; Widanaputra, A.A.G.P. (E-Jurnal Akuntansi, 2017)
The world of education today many things that must be considered to create qualified students who can understand the lessons given by lecturers, especially in terms of teaching systems that have been delivered by lecturers in class and quality of the lessons given by lecturers. The lack of concentration of student learning especially in the class whereas the concentration of learning is very necessary and will affect the learning outcomes achieved. Concentration of learning is a personal self-focus of students on the course or learning activities and lectures activities. Undergoing lecture activity is needed full concentration to get a very satisfactory results. The purpose of this study is to obtain empirical evidence of the influence emotional intelligence, intellectual intelligence, and learning behavior at the level of accounting understanding in non-regular students majoring in accounting class Faculty of Economics and Business Udayana University. This study uses primary data collected by using questionnaires as an instrument of data collection distributed to respondents. Respondents of this study are non-regular students majoring in accounting class of 2013 Faculty of Economics and Business Udayana University. The number of samples obtained is 170 samples. Data analysis technique used is multiple linear regression analysis. The results showed that emotional intelligence has positive effect , intellectual intelligence has positive effect, and learning behavior has positive effect on the level of accounting understanding.